On the specific elastic energy capacity of rocks in the earth's crust of Ukraine - V. V. Gordienko (Геофизический журнал, 2012)
The values of specific elastic energy-capacity of the earths crust rocks of Ukraine are examined at the depth of 10 km. Most earthquake foci are approximately at this depth. The parameter varies between (1,3-1,8) 106 J/m3. The variations are mainly related to the temperature of rocks. It is shown that specific elastic energy capacity is in good agreement with the seismic moment and volume of the seismic focus.